Prediction of Rheological Properties and Interfacial Tension of Mixtures of Immiscible Polypropylene-Polystyrene (PP3/PS) Blends - BOUDOUKHANI, Meriem; MOULAI-MOSTEFA, Nadji; HAMMANI, Salim (Walailak Journal of Science and Technology (WJST), 2020)
Blends of polypropylene (PP3) and polystyrene (PS) were studied and, their rheological behavior was determined and discussed in detail. The interfacial tension between the blend components was evaluated from the rheological data and the storage modulus by using two well-known models: Palierne model and Choi-Schowalter equation. The theoretical predictions were compared with experimental data obtained from PP3/PS blends. The obtained results showed that the Palierne model could predict the rheological and viscoelastic properties of the considered polymer blends. In addition, the interfacial tensions between PP3 and PS were evaluated and compared with those cited in the literature. It was also found that the Palierne model was more accurate than Choi-Schowalter one in determining the interfacial tension.